2014
DOI: 10.1016/j.bcmd.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphisms at BCL11A, HBS1L-MYB and Xmn1-HBG2 site loci associated with fetal hemoglobin levels in sickle cell anemia patients from Northern Brazil

Abstract: Increased levels of fetal hemoglobin (HbF, α2γ2) may reduce sickle cell anemia severity due to its ability to inhibit HbS polymerization and also reduce the mean corpuscular HbS concentration. We have investigated the influence of three known major loci on the HbF trait (HBG2, rs748214; BCL11A, rs4671393; and HBS1L-MYB, rs28384513, rs489544 and rs9399137) and HbF levels in SCA patients from the State of Pará, Northern Brazil. Our results showed that high levels of HbF were primarily influenced by alleles of BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 15 publications
5
26
1
Order By: Relevance
“…Minor allele frequencies (MAFs) of relevant variants rs4671393 at BCL11A (Table 1) were similar to those detected in African Americans [3] or Brazilian [1,3]; and the relationships with HbF were significant (P b .001), but explained less of the variance in HbF (~2% vs 10%) [1][2][3]. It is possible that other genomic polymorphisms in these loci need to be investigated in West African SCD patients; indeed a recent report has shown that common variations at BCL11A that had a stronger association with HbF levels lie in noncoding sequences associated with an erythroid enhancer [4].…”
Section: To the Editorsupporting
confidence: 65%
See 2 more Smart Citations
“…Minor allele frequencies (MAFs) of relevant variants rs4671393 at BCL11A (Table 1) were similar to those detected in African Americans [3] or Brazilian [1,3]; and the relationships with HbF were significant (P b .001), but explained less of the variance in HbF (~2% vs 10%) [1][2][3]. It is possible that other genomic polymorphisms in these loci need to be investigated in West African SCD patients; indeed a recent report has shown that common variations at BCL11A that had a stronger association with HbF levels lie in noncoding sequences associated with an erythroid enhancer [4].…”
Section: To the Editorsupporting
confidence: 65%
“…Interestingly, contrary to the data reported by Cardoso et al, the largest allelic effect was detected in Cameroonian patients, at the HBS1L-MYB locus rs9399137 (effect size: 0.412; SE: 0.1562) and explained 1.6% of HbF variance as compared to 0% in the Brazilian cohort (Table 1). This cannot be attributed to the frequency of the rs9399137 MAF that was relatively low in both patients' group (0.04 in Cameroonians and 0.08 in Brazilian), or any European genetic admixture among this group of Cameroonian since rs9399137 acts as a tagging SNP for the HMIP-2 sub-locus in European populations [5], but possibly by the modest sample size of the Brazilian cohort reported by Cardoso et al [1]. However, we previously reported in the HMIP-2 sub-locus, a much higher frequency of rs9389269 (0.18) in Cameroonian [2] as compared to the Tanzanian SCD patients (0.03) [6].…”
Section: To the Editormentioning
confidence: 56%
See 1 more Smart Citation
“…25 More recently, SNPs in the HMIP region were shown to be associated with HbF levels in SCD patients from Tanzania, 26 Northern Brazil, and Cameroon. 63,64 The ability of MYB to regulate HbF production in erythroid cells 65 has been demonstrated. Subsequently, Stadhouders et al described an erythroidspecific enhancer located in the HMIP region that regulates MYB expression.…”
mentioning
confidence: 99%
“…Dependent upon the genetic variants investigated and analysis performed, such variants were found to account for between 8 and ;20% of the HbF variability in SCD in studies from the United Kingdom, United States, Brazil, Tanzania, and Cameroon. [6][7][8][9][10][11][12][13] This genetic component is likely to account for much of the variability in HbF levels in SCD patients. Consequently, it may be helpful to quantify and summarize the effects of the respective genetic loci into a single genetic variable to capture the essence of genetic disease alleviation through the HbF mechanism.…”
Section: Introductionmentioning
confidence: 99%